Tilted electric-field and hydrostatic pressure effects on donor impurity states in cylindrical GaAs quantum disks (2008)
ABSTARCT: In this work we are devoted to the study of donor impurity states in a cylindrical GaAs quantum disk under the effects of tilted applied electric field and hydrostatic pressure. A variational procedure has been performed within the effective mass and parabolic-band approximations. For the hydrostatic pressure effects we consider the Γ-X mixing via a phenomenological procedure.